The effects of teachers overworking on educational activity - Rus, Mihaela; Sandu, Mihaela Luminița; Băltărețu (Peiu), Veronica (Technium Social Sciences Journal, 2022)
This research investigates teachers overworking and associated stress. Teachers must deal with mixed, profound types of interactions and respond to requests by colleagues, managers, parents, and community members. The work of teachers is very complex, especially in the classroom, because it requires to be constantly alert to everything that happens in there both in terms of student behavior, their emotions and their accumulation of knowledge. Teachers spend a good part of their time at work, being involved in relationships both with the beneficiaries of the services provided (students) and with other teachers, principals, inspectors etc.. All these relationships require a great deal of emotional effort, intellectually, mentally and even physically. At the same time, the teaching activities (teaching, guidance, evaluation) also require a lot of effort. It takes several hours of study to prepare for the lesson, and over time it is time-consuming, with teachers often giving up personal activities in order to perform their duty. Teachers overworking occurs when they cannot achieve a balance between the many demands they have to face: professional, social, family and they feel that they cannot give enough time to any of them. They report experiencing very high stress related to overworking. Action can be taken once the effects of teachers overworking are understood.